Numerical simulation of P91 steel under low-cycle-fatigue loading - M. A. A., Roslin; Norhaida, Ab Razak; Nasrul Azuan, Alang; Norazlianie, Sazali (Springer Nature, 2023)
Increased worldwide power consumption in the twenty-first century reflects industry progress and economic expansion. This increases the demand for electricity from power plants, which raises their operating conditions and parameters thus requiring high-performance steel to be used. P91 steel is the best selection material as it poses excellent thermal conductivity, low thermal expansion coefficient, and high corrosion resistance. However, the material component is exposed to mechanical and temperature cycling, which creates thermal gradients on the components and may generate high cyclic stress levels between the components, which may cause cracks in the structure of the components and body damage. Prolonged exposure of the material to cyclic loading may result in low-cycle fatigue which may cause thermo-mechanical fatigue failure to the components. The low-cycle fatigue test is costly and time- consuming. Therefore, the use of the finite element approach in material analysis can be helpful to examine the behavior of steel specimens when subjected to low-cycle fatigue. The cyclic stress–strain response was replicated by using the constitutive model of combination isotropic–kinematic hardening implemented in the finite element software Abaqus. The development of the material model for the numerical simulation is based on a previous study where the parameters for the experimental low-cycle fatigue tests were extracted to be used in the calculation for the simulation. The combined hardening parameters were developed, and the isotropic and kinematic hardening parameters were calculated. The simulation uses strain amplitude varying between 0.25 and 0.6% with a constant strain rate of 0.1%s-1 at room temperature. The stress amplitude of the material decreases as the number of cycles increases which shows that the material exhibits cyclic softening in cyclic loading. Cyclic softening behavior is more noticeable with higher strain amplitude as it resulted in lower fatigue life. Higher strain amplitude resulted in higher peak stress and plastic strain. The finite element analysis of the low-cycle-fatigue P91 steel is relatively like the experimental results which also can give a significant understanding of the usage of P91 steel to industrial applications.